Improving Wellness for LGB Collegiate Student-Athletes Through Sports Medicine: A Narrative Review - Mikalyn T. DeFoor; Lara M. Stepleman; Paul C. Mann (SpringerOpen, 2018)
Abstract In comparison to their heterosexual peers, lesbian, gay, and bisexual (LGB) student-athletes encounter substantial challenges during their intercollegiate and professional athletic careers including detrimental stereotypes, harassment, and discrimination. Such non-inclusive environments promoted throughout the current Western culture of sport are notably associated with higher incidences of mental health and substance use disorders among LGB athletes across youth, collegiate, and professional sports. There have been significant gains at the collegiate level to address LGB-inclusive practices aimed towards administrators, educators, coaches, and student-athletes; however, there is currently no literature that addresses the unique role of the sports medicine team. As first-line healthcare providers for student-athletes, sports medicine physicians and athletic trainers are uniquely positioned to support collegiate LGB athletes through affirming sexual identity, recognizing distinctive health risks, and advocating inclusivity within the athletic training room. By examining major themes of concern among current LGB student-athlete experiences across the unique setting of US colleges and universities, this review article aims to further identify opportunities for sports medicine providers to promote positive health outcomes and improve the overall wellness of collegiate LGB student-athletes.